Orofacial harmonization and the interrelation with implantology: A literature review (Research, Society and Development, 2021)
Introduction: Tooth loss directly influences the functions of the stomatognathic system and through Implantology it is possible to reestablish the patient's masticatory and phonetic function, also contributing to the improvement of facial aesthetics. highlighted for helping directly in the cases of rehabilitation promoting considerable functional and aesthetic improvements. Objective: To evaluate the contribution of Orofacial Harmonization to rehabilitation with dental implants through a literature review. Methodology: A bibliographic review of the literature of a basic nature and with qualitative analysis of the data was carried out. The search was carried out on the digital platforms of PubMed and Google Scholar during the period from November to December 2020, using as main terms "Facial Harmonization", "Implantology", "Rehabilitation", and free terms, in English and Portuguese without filters yearly. Results: It was observed that Botulinum Toxin (TB) and Hyaluronic Acid (HA), substances used in HOF, contribute positively to implantology, favoring the results related to stabilization, osteointegration, reduction of occlusal overloads and, through muscle injections, they work well in patients with parafunctional habits, reducing overloads that lead to implant failure. Still, there was an improvement in the red aesthetic, optimizing the aesthetic results of the blackspaces. Conclusions: HOF contributes to the optimization of implant results in aesthetics and function. Until the moment of bibliographic consultation, laser therapy, HA and TB are directly linked to implantology. However, due to the variety of existing substances, it appears that more studies are needed that associate the other substances to dental implants.